A fatal balancing act : the dilemma of the Reich Association of Jews in Germany, 1939 - 1945 - Meyer, Beate 1952- (Berghahn, 2013)
In 1939 all German Jews had to become members of a newly founded Reich Association. The Jewish functionaries of this organization were faced with circumstances and events that forced them to walk a fine line between responsible action and collaboration. They had hoped to support mass emigration, mitigate the consequences of the anti-Jewish measures, and take care of the remaining community. When the Nazis forbade emigration and started mass deportations in 1941, the functionaries decided to cooperate to prevent the "worst." In choosing to cooperate, they came into direct opposition with the interests of their members, who were then deported. In June 1943 all unprotected Jews were deported along with their representatives, and the so-called intermediaries supplied the rest of the community, which consisted of Jews living in mixed marriages. The study deals with the tasks of these men, the fate of the Jews in mixed marriages, and what happened to the survivors after the war. -- Provided by publisher.